Effect of Ca modification on the catalytic performance of Ni/AC for CO2 methanation. Issue 172 (12th June 2016) - Feng, Yanyan; Yang, Wen; Chu, Wei
Abstract: The effect of Ca content on the CO2 methanation performance of the NiCa/AC catalysts was studied in detail. The addition of Ca can effectively restrain the growth of NiO nanoparticles and improve the dispersion of NiO. The results showed that the NiCa/AC catalysts with a nickel content of 15 wt.% had better catalytic activities than that of pure Ni/AC, and the modified catalyst with 10 wt.% Ca had the highest catalytic activity among the tested catalysts.